Multicenter ALK testing in non-small-cell lung cancer: results of a round robin test - Laffert, Maximilian von; Penzel, Roland; Schirmacher, Peter; Warth, Arne; Lenze, Dido; Hummel, Michael; Dietel, Manfred (Journal of thoracic oncology, 2014)
Background - The anaplastic lymphoma kinase (ALK) inhibitor crizotinib has recently received approval for the treatment of patients with locally advanced or metastatic ALK-positive non-small-cell lung cancer (NSCLC). As the therapeutic prescription postulates the detection of ALK rearrangements, reliable diagnostic approaches are of utmost importance. With this study, we present the data of the first German ALK-round robin test based on genomic DNA in situ hybridization (ISH). The application of immunohistochemistry (IHC) for ALK protein detection was optional and not required for certification. - Methods - Two tissue microarrays, each consisting of the same 10 NSCLC but in different arrangement of the cases, were generated (five unequivocally ALK-positive and five unequivocally ALK-negative cases). ISH-based results and optional IHC data had to be submitted within 10 working days. A successful participation (certification) was reached if at least 19 of the 20 possible points were scored (2 points for a correct case classification). - Results - Fifty-three of 59 participants (89.8%) provided their data for ISH-ALK detection within the submission period. Thirty-two of 53 participants (60.3%) received at least 19 points required for certification. Remarkably, the range of cells with aberrant ALK signal configuration was broad in ALK-negative (0-13%) and in ALK-positive cases (15-95%). Thirty-five participants supported the round robin test with optional ALK IHC results, which displayed a great heterogeneity in the ALK ISH-positive cases. - Conclusion - In essence, our ALK ISH round robin test clearly demonstrates that there is accumulating need for improvement of ALK testing. Although ISH may be regarded as a well-established procedure, its broad application in a diagnostic setting is challenging and requires standardized methods and harmonized interpretation to achieve sound results for therapeutic decisions. The same is true for ALK IHC which, however if standardized, might improve the diagnostic approach.
Available online 20 November 2015
Gesehen am 16.07.2020